A practical review of energy saving technology for ageing populations. (July 2017) - Walker, Guy; Taylor, Andrea; Whittet, Craig; Lynn, Craig; Docherty, Catherine; Stephen, Bruce; Owens, Edward; Galloway, Stuart
Abstract: Fuel poverty is a critical issue for a globally ageing population. Longer heating/cooling requirements combine with declining incomes to create a problem in need of urgent attention. One solution is to deploy technology to help elderly users feel informed about their energy use, and empowered to take steps to make it more cost effective and efficient. This study subjects a broad cross section of energy monitoring and home automation products to a formal ergonomic analysis. A high level task analysis was used to guide a product walk through, and a toolkit approach was used thereafter to drive out further insights. The findings reveal a number of serious usability issues which prevent these products from successfully accessing an important target demographic and associated energy saving and fuel poverty outcomes. Design principles and examples are distilled from the research to enable practitioners to translate the underlying research into high quality design-engineering solutions. Highlights: The mass market in home energy saving devices for elderly users is being badly served. 12 products were formally evaluated and all were revealed to have severe usability issues. Design principles and practical solutions are put forward to address this shortfall.